التعليم العام المركزية واللامركزية في الإدارة التعليمية - العرفج، نورة سعد (المؤسسة العربية للتربية والعلوم والآداب, 2020)
المركزية واللامركزية أسلوبين من أساليب التنظيم الإداري ولا يمكن الأخذ بأحدهما بشكل مطلق، بمعنى أن المركزية الكاملة أو اللامركزية الكاملة لا يمكن أن يتحققا في الواقع العملي، فالمشكلة ليست الاختيار بينهما ولكن في كيفية الجمع بينهما، فاللامركزية ما هي إلا عملية نقل للسلطات ما بين الحكومة المركزية والأجهزة المحلية، وبالتالي فإن مقياسنا في المركزية أو اللامركزية هو قياس القرارات التي تتخذ في الأجهزة المركزية، وكلما كانت القرارات التي تتخذ في المحليات أكثر وأقوى ولها الفاعلية الأكبر فإننا نكون متجهين نحو اللامركزية، وإذا أمكننا تنظيم الوحدات المركزية أمكن تنفيذ اللامركزية تنفيذا سليما وفعالا. ويتضح لنا التوجه الحديث باللجوء إلى اللامركزية في التعليم، وقد ذكرنا الأسباب والمبررات لذلك، لكن يجب أن نذكر بأن تطبيق اللامركزية يحتاج إلى ضوابط لتنظيمه حتى يحقق النتائج المرجوه منه. وفي حال عدم تطبيقه بالطريقة المناسبة سوف يؤدي إلى نتائج عكسية على مستوى جودة التعلم.
Centralization and decentralization are two methods of administrative organization and one cannot be taken entirely, meaning that complete or complete decentralization cannot be achieved in practice, the problem is not a choice between them, but how to combine them, so decentralization is only a transfer of powers between the central government and local bodies And therefore, our measure of centralization or decentralization is the measurement of decisions taken in central agencies, and the more decisions that are made in localities are more and more powerful and have greater effectiveness, we are heading towards decentralization, and if we can organize bitter units Uniform implementation of the decentralization Aomcn implementation of sound and effective. It is clear to us the modern approach to resort to decentralization in education, and we have mentioned the reasons and justifications for that, but we must mention that the application of decentralization requires controls to regulate it in order to achieve the desired results. Failure to apply it in the appropriate manner will lead to adverse results in the quality of learning
Keywords: التعليم العام -- جودة التعليم -- المؤسسات التعليمية -- الإدارة التعليمية -- المركزية -- اللامركزية